Melting of phase change materials in a trapezoidal cavity: Orientation and nanoparticles effects - lachachene, Farida; Haddad, Zoubida; Öztop, Hakan Fehmi; Abu-Nada, Eiyad (Elsevier, 2019)
A transient two-dimensional numerical study based on the enthalpy-porosity technique was carried out on the melting of a phase change material (PCM) embedded in a trapezoidal cavity. First, the cavity was filled with paraffin wax to study the orientation effect on the performance of the PCM. Then, graphene nanoparticles are dispersed into the pure PCM to determine to what extent the nanofluid thermal performance could balance the enhancement associated with the orientation effect, hence, a comparison between both effects was conducted and discussed. Experimental data for the latent heat of fusion and solid nano-enhanced phase changed material (NEPCM) thermal conductivity were used instead of simple mixture models or correlations. The temporal velocity and temperature profiles were shown in addition to the melt fraction as a function of the melting time. The simulated results clearly demonstrated that both effects are beneficial for heat transfer enhancements in PCMs. However, NEPCM lead to a lower heat transfer performance when the nanofluid thermal conductivity enhancement was <80%. (C) 2019 Published by Elsevier B.V.
Keywords: Melting; Nanoparticles; Trapezoidal cavity; PCM; NEPCM; Computational fluid dynamics (CFD)